A novel multi-objective optimization strategy for enhancing quality of service in IoT-enabled WSN applications - Prasanth, A.; Jayachitra, S. (Peer-to-peer networking and applications, 2020)
In today’s world, the Internet of Things (IoT) has become more relevant owing to the growth in smart grid, smart city and smart home applications. Network sustainability is considered as a significant characteristic for IoT based applications. Wireless Sensor Network (WSN) offers such network sustainability where WSN is acted as the subnets in the IoT model. However, the multi-objectives like coverage, connectivity and energy consumption are required to improve the quality of service in IoT based WSN (IWSN) model. An appropriate optimization strategy of these multi-objective facilitates the better development of IWSN. In this paper, the Adaptive Coverage and Connectivity (ACC) scheme is proposed to attain the efficient IWSN model. It employs two underlying methodologies in which the first method provides the optimal coverage to all target objects and its mathematical model guarantees the coverage rate. The second method deals with connectivity and energy consumption of the network. The experimental results manifest that, unlike existing schemes, the proposed ACC scheme can sustain the network for a prolonged time.